A NOVEL KCNJ11 MUTATION ASSOCIATED WITH CONGENITAL HYPERINSULINISM REDUCES THE INTRINSIC OPEN PROBABILITY OF β-CELL ATP-SENSITIVE POTASSIUM CHANNELS - Lin, Yu-Wen (2005)
The β-cell ATP-sensitive potassium (K(ATP)) channel controls insulin secretion by linking glucose metabolism to membrane excitability. Loss of K(ATP) channel function due to mutations in ABCC8 or KCNJ11, genes that encode the sulfonylurea receptor 1 or the inward rectifier Kir6.2 subunit of the channel, is a major cause of congenital hyperinsulinism. Here, we report identification of a novel KCNJ11 mutation associated with the disease that renders a missense mutation, F55L, in the Kir6.2 protein. Mutant channels reconstituted in COS cells exhibited wild-type like surface expression level and normal sensitivity to ATP, MgADP, and diazoxide. However, the intrinsic open probability of the mutant channel was greatly reduced, by ~10-fold. This low open probability defect could be reversed by application of phosphatidylinositol 4,5-bisphosphates or oleoyl CoA to the cytoplasmic face of the channel, indicating that reduced channel response to membrane phospholipids and/or long chain acyl CoAs underlies the low intrinsic open probability in the mutant. Our findings reveal a novel molecular mechanism for loss of K(ATP) channel function and congenital hyperinsulinism, and support the importance of phospholipids and/or long chain acyl CoAs in setting the physiological activity of β-cell K(ATP) channels. The F55L mutation is located in the slide helix of Kir6.2. Several permanent neonatal diabetes-associated mutations found in the same structure have the opposite effect of increasing intrinsic channel open probability. Our results also highlight the critical role of the Kir6.2 slide helix in determining the intrinsic open probability of K(ATP) channels.